A study to screen infertile couples for psychological problems by using the perceived stress scale, brief COPE scale and hospital anxiety and depression scale - Singh, Vikas; Bhirud, Yogesh Rajesh; Lele, Prasad; Bhagasra, Santosh (International Journal of Research in Medical Sciences, 2021)
Background: Infertility refers to the biological inability of a couple to contribute towards conception, or the state of a woman, who is unable to carry a pregnancy to full term. Though infertility is not only a disease per se it embraces a wide spectrum, but its treatment also affects all aspects of people’s lives. Aim of the study was to screen infertile couples for psychological problems, and to identify various psychological problems and factors associated with these problems. Methods: It was a cross-sectional study with total of 270 consecutive couples (patients) either of them diagnosed with infertility. All the patients who were found to have anxiety and depression score above seven were then interviewed by the psychiatrist for anxiety and depression. Results: Mean age of the males and females was 32.2 years and 29.7 years, respectively. Duration of marriage was less than five years in 37% couples while it was more than ten years in 19.6% couples. The major cause of infertility was identified in about two-thirds of the cases (64.1%). Prevalence of anxiety was observed in 49.6% females and 45.6% of males. Prevalence of depression was significantly higher among females (41.9%) as compared to males (37%). Conclusions: The present study has endeavored to draw attention to the interrelation of anxiety and depression among infertile couples. Apart from searching for the gynecological causes of infertility; psychological morbidity should be considered as a serious concern affecting these women.